An assessment of community pharmacists' attitudes towards professional practice in the Republic of Moldova. - Cordina M; Safta V; Ciobanu A; Sautenkova N. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Pharmacy in Moldova is undergoing a period of transition. The professional practice is adjusting to a market-oriented economy from the previous Soviet system. The pharmaceutical sector has been liberalised giving rise to a significant increase in the number of community pharmacies. This has led to some adverse effects on the profession of pharmacy with pharmacists having considerable difficulties fulfilling their professional aspirations and possibly losing confidence in further developing their professional role. Objective: To assess community pharmacists' attitudes towards their professional practice and to determine their perceived competence in various pharmaceutical activities.Methods: A questionnaire which addressed managerial activities, dispensing activities, pharmaceutical care activities, inter-professional relationships, public health and competence was mailed to 600 community pharmacists who were asked to score the importance and perceived competence for each activity on a scale ranging from 0-5. In the case of pharmaceutical care activities, pharmacists were asked to score their degree of agreement or disagreement as to whether it is the responsibility of the pharmacist to engage in specific pharmaceutical care activities.Results: A total of 370 valid questionnaires were returned giving a response rate of 61.7%. Managerial and dispensing activities were scored the highest both in terms of perceived importance and competence. The more innovative pharmaceutical care activities scored relatively low. Overall scores relating to the importance of pharmacists engaging in public health activities appear to be the lowest of the entire questionnaire. Younger pharmacists between the ages of 22-30 obtained significantly higher scores with regards to the perceived pharmacist's responsibility in engaging in various pharmaceutical care activities. Respondents who practiced in an accredited pharmacy scored higher in the majority of questions.Conclusion: Pharmacists in Moldova appear to be deeply rooted in the traditional approach to the practice of pharmacy pertaining mainly to distributive practice model and are somewhat distant from the other models of practice such as pharmaceutical care, drug information and self-care.